DOCTOR AND PATIENT: FEATURES OF RELATIONSHIPS AND TRUST - Ibragimova Dilbar Sadullaevna; Mukhamadieva Muhabbat (Research Focus International Scientific Journal, 2025)
The relationship between a doctor and a patient is the most important aspect of medical practice, directly affecting the quality of diagnosis, treatment and rehabilitation. The basis of effective interaction is trust, which is formed on the basis of the doctor’s professional competence, his communication skills, adherence to medical ethics and respectful attitude towards the patient. Particular attention is paid to modern challenges in medical practice, including the impact of digital technologies and the development of telemedicine.